Low Transportation Emission Analysis and Projection Using LEAP: The Case of Qatar - Maryam Al-Jabir (19171159) (2023)
The transportation sector is a significant source of pollution and greenhouse gas (GHG) emissions contributing to global warming. Although research on the actual emissions from transport has been conducted in several parts of the world, very limited outcomes in this field have been reported in the Gulf region. This is especially true for road transportation, one of Qatar’s most significant sources of air pollution. To address this research gap, this study provides an invaluable resource for policymakers as it is the first to quantify the current and forecast future transport emissions. In this work, actual data on traffic counts were input into the Low-Emissions Analysis Platform (LEAP) tool, which has never been used in the context of Qatar, making it an outstanding addition to the research in this domain. The ultimate goal is to estimate the transportation emissions from road traffic in Qatar and investigate how different actions lead to three different scenarios that can impact it. Considering that the policy reformation in the transportation sector is crucial to reducing greenhouse gas emissions and climate change, a scenario analysis can provide theoretical support for policy development and implementation. The investigation used the actual vehicle count data from 2017 to 2021, while all future projections considered the duration from 2022 to 2050 using three scenarios. The first was based on the historical growth in the number of vehicles; the second was based on the business-as-usual scenario (BAU); and the third considered that the public transport shall be divided into three sub-scenarios, namely fuel-economy improvement, the electrification of public transportation, and the replacement of diesel or petrol fuel with compressed natural gas (CNG). The results show that carbon dioxide (CO2) emissions were the highest in all scenarios. Moreover, it was found that in the BAU, the light-duty vehicles (LDVs) category is the most significant contributor to GHG emissions compared to motorcycles and heavy-duty vehicles (HDVs). In addition, it was found that emissions can be reduced by improving public transportation, switching to a cleaner fuel, and reducing reliance on private vehicles. Other Information Published in: Atmosphere License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/atmos14081286